Genome-Scale Phylogenetic and Population Genetic Studies Provide Insight Into Introgression and Adaptive Evolution of Takifugu Species in East Asia - Liu, Bo; Zhou, Zhixiong; Bai, Yulin; Yang, Junyi; Shi, Yue; Pu, Fei; Xu, Peng (Frontiers in Genetics, 2021)
As a typical marine adaptive radiation spec¬¬¬ies, most Takifugu species are widely distributed in East Asian offshore, which have diversified morphological characteristics and different ecological habits. The phylogenetic relationship and population structure of the Takifugu species was complicated because of incomplete lineage sorting, widespread hybridization and introgression. Therefore, to systematically clarify the phylogenetic relationships of Takifugu genus, explore the introgression and natural hybridization between different Takifugu species, and detect the selective signatures in the adaptive evolution of diversified traits, whole-genome resequencing was used in 124 Takifugu samples from 10 species. Phylogenetic analysis showed solid sister-group relationships between Takifugu bimaculatus and Takifugu flavidus, Takifugu oblongus and Takifugu niphobles, Takifugu rubripes and Takifugu obscurus, Takifugu xanthoptreus and Takifugu ocellatus. Further admixture analysis indicated the divergence of T. obscurus population and the bidirectional gene flow between T. bimaculatus and T. flavidus. Using species-specific homozygous genetic variance sites, we detected the asymmetric introgression between T. bimaculatus and T. flavidus at China East sea and southern Taiwan Strait. By genome-scale genetic diversity scanning, we detected two copies of syt1, zar1 and tgfbr1 related to the semilunar reproduction rhythm in T. niphobles, involved in memory formation, embryo maturation and female reproduction. Furthermore, we also found lots of T. niphobles specific mutations in CDS region of circadian rhythm related genes and endocrine hormone genes. For Takifugu species, our research provides reliable genetic resources and results for the phylogeny, introgression, hybridization and adaptive evolution, and could be used as a guide for the formulation of the protection and proliferation release policies.